Telecommunications cost management - Strother, S. C. (Artech House telecommunications library., 2002)
Here's a practical cost management guide to the complex world of voice, data and wireless telecommunications for the non-technical business professional. Examining the complex, highly technical telecommunications industry from an insider's point of view, it sifts through all the technical jargon, offers a comprehensive education on the applications, services and procurement of telecom products, and provides a strategy to effectively manage the costs of those products and services. The book enables you to: understand telecom services; audit phone bills; reduce the cost of existing services and eliminate unnecessary ones; and efficiently negotiate new contracts and services.